Effectiveness Analysis of Single Dose Rifampicin-Post-Exposure Prophylaxis (SDR-PEP) as A Preventive Intervention for Leprosy Transmission: A Systematic Review of Randomized Controlled Trials - Asyura, Muhammad Mikail Athif Zhafir; Wijaya, Ilma Ranjani; Toshukowong, Theetouch; Wang, Rui Sheng (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: Leprosy is a skin disease that reaches 200,000 cases annually. Considered a neglected tropical disease, 80% of annual leprosy remained in countries such as Brazil, India, and Indonesia. Multi-drug treatment is effective in curing leprosy but ineffective in preventing further transmission. The implementation of large-scale single dose rifampicin-post exposure prophylaxis suggests the inhibition of leprosy transmission and thus needs validation.Methods: This systematic review was carried out based on the PRISMA statement from multiple databases using set keywords. A total of 646 studies were identified, followed by 4 randomized controlled trials included after screening.Results: 86,502 subjects were divided into control and interventional groups and were to be followed up in 2-6 years. Most studies showed a significant decrease of leprosy cases by 50-60%. Furthermore, a complementary effect between single-dose rifampicin-post exposure prophylaxis and Bacillus Calmette–Guérin vaccine was identified. Moreover, the cost-effectiveness of the intervention was analyzed which resulted in IDR 80,414,775 being averted in its 25th year of implementationConclusion: The review established promising results of implementing single dose rifampicin-post exposure prophylaxis to prevent leprosy transmission. Further national scale intervention with a multi-layered approach is suggested to ensure full support and continuity of the large-scale intervention